ANALISIS CHURN PADA JASA BROAD BAND TELEKOMUNIKASI SELULAR DI SUMBAGUT - Radius Poniman; Opim Salim; Sri Mulyani (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2015)
Mobile telecommunications have a significant influence in the lives ofmany people around the world. One of the services that are projected will determinethe survival of the organization of the providers of cellular telecommunicationsservices are broadband services. On the other hand, tough competitionin the mobile telecommunications industry in Indonesia has resulted inhigh customer churn rate. Churn is a representation of the consumer switchingbehavior. The switching behavior is partly due to three factors namely consumerdissatisfaction, situational conditions, and Switching Cost. ParametersSimultaneously Attached Users Sumbagut customers Telkomsel data showed adecline in the first quarter of 2014, this parameter as one of the indicators ofchurn. This study aims to determine the significance of these three factorsinfluence the behavior of consumers switching broadband mobile telecommunicationsservices in Sumbagut. The results showed that the overall contributionof the influence of the independent variables of consumer dissatisfaction,situational conditions, and Switching Cost jointly to switch on the consumerbehavior in Sumbagut broadband services amounted to 74.1%. Remaining acontribution of 25.9% is determined by other factors besides predictor containedin this research model. The study then showed that consumer dissatisfactionvariable (β = 1,126) and situational conditions (β = 0948) significantly affectscustomer switching behavior broadband services. Variable Switching Cost nosignificant effect on the behavior of the switch, which is caused by the characteristicsof broadband services that have a low level because of the relationalnature of its services in the form of a 'one-way interaction'. Value Odds Ratioconsumer dissatisfaction is 1,126 and situational conditions of 1012.Keywords: Jasa Broadband, Simultaneously Attached Users, Churn